2016
DOI: 10.1055/s-0036-1579746
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of En Bloc Vertebrectomy Compared with Intralesional Resection for Giant Cell Tumors of the Mobile Spine

Abstract: Study Design Systematic review and meta-analysis. Objective To compare the recurrence and perioperative complication rate of en bloc vertebrectomy (EV) and intralesional resection (IR) in the giant cell tumor of the mobile spine (SGCT). Methods We systematically searched publications in the PubMed and Embase databases for reports of SGCTs, excluding the sacrum. Two reviewers independently assessed all publications. A meta-analysis was performed using local recurrence and postoperative complications as the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
0
24
1
2
Order By: Relevance
“…In future cases, consideration should be given to using prosthetic mesh alone to reduce surgical time, a composite of a latissimus dorsi muscle flap and prosthetic mesh so that there are two supplementary reconstruction techniques in case one fails, or a latissimus dorsi myocutaneous flap, with or without additional prosthetic mesh, to improve perfusion of the latissimus dorsi muscle. Despite the risk of complications with total en bloc vertebrectomies with experienced surgeons in high‐volume centres, in one meta‐analysis, the postoperative complication rate was greater in patients treated with intralesional resections (36.4%) compared with patients treated with en bloc vertebrectomies (11.1%)13; so a less aggressive resection has minimal benefits with a higher complication rate and higher risk of local tumour recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In future cases, consideration should be given to using prosthetic mesh alone to reduce surgical time, a composite of a latissimus dorsi muscle flap and prosthetic mesh so that there are two supplementary reconstruction techniques in case one fails, or a latissimus dorsi myocutaneous flap, with or without additional prosthetic mesh, to improve perfusion of the latissimus dorsi muscle. Despite the risk of complications with total en bloc vertebrectomies with experienced surgeons in high‐volume centres, in one meta‐analysis, the postoperative complication rate was greater in patients treated with intralesional resections (36.4%) compared with patients treated with en bloc vertebrectomies (11.1%)13; so a less aggressive resection has minimal benefits with a higher complication rate and higher risk of local tumour recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown a significantly improved outcome in patients treated with en bloc vertebrectomy in comparison to less aggressive surgical techniques,7 11–19 even if histologic margins are incomplete 7 12 16. In one multicentre cohort study investigating the Enneking classification of surgical margins for resection of musculoskeletal tumours in the management of primary vertebral tumours,19 the local recurrence rate was significantly higher in patients in the Enneking inappropriate group (74%) compared with the Enneking appropriate group (20%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Charest‐Morin et al ., surgical margins have an important impact on local recurrence, and en bloc resection with wide/marginal margins may be associated with lower local recurrence and better prognosis7, 18. One systematic review and meta‐analysis also supported that SGCT patients treated with en bloc vertebrectomy had a lower recurrence rate19. Meanwhile, Boriani et al .…”
Section: Discussionmentioning
confidence: 99%
“…En bloc resection is associated with decreased local recurrence rate and mortality7, 18, 19. The management of recurrent SGCT is relatively difficult and there is little published literature on the subject11, 37.…”
Section: Discussionmentioning
confidence: 99%